Linguistics : an introduction to language and communication - Akmajian, Adrian; Demers, Richard A.;Harnish, Robert M. (Cambridge, Massachusetts : The MIT Press, 1984)
This second edition of our text evolved from our continuing collaboration in teaching introductory linguistics at the University of Arizona.
Part One. Background -- Part Two. The structure of human language -- Part Three. Communication and cognitive science.
Includes index.
Keywords: LINGUISTICS